Cattle rumen tissue arginase and molecular weights of its subunits - Erisir, M; Ozan, ST (Scientific Technical Research Council Turkey, 2003)
The arginase was partially purified from cattle rumen tissue and its properties were investigated and thereafter compared with those of other tissue arginases. The specific activity of the purified enzyme was found about 150 times greater than that of the crude rumen homogenate. The molecular weight of native arginase, estimated by gel filtration on a Sephadex G-150 column, was 122 500 +/- 2500 and those of subunits of the enzyme, estimated by SDS-PAGE and gel filtration on a Sephadex G-100 column, were 44 000 +/- 1000 and 34 500 +/- 500. This indicates that the native enzyme is a trimer composed of subunits with two different molecular weights. The enzyme was unstable because it gradually lost its activity in a freezer, at +4 degreesC and room temperature. The enzyme lost 50% of total activity in 9 days at -30degreesC (in the freezer). The presence of a single anionic form of arginase in cattle rumen tissue was demonstrated by DEAE-sephacel chromatography. Cattle rumen tissue arginase contains only one isoenzyme. Arginase isolated from cattle rumen tissue may be arginase A(4) or A(2) form when it is compared with those of other tissue arginase isoenzymes.
Si?ir rumen doku arginazi ve subünitelerinin molekül a?irli?i
Keywords: cattle rumen tissue; arginase; subunit; molecular weight